DIGITAL SIGNAGE : MAKNA, STRATEGI PEMBUATAN PESAN, DAN IMPLEMENTASI OLEH DENTSU AGENCY - Karina Pramita Ningrum (Media Bahasa, Sastra, dan Budaya Wahana, 2022)
AbstractThis article discusses the digital signage: meaning, message creating strategy and implementation by Dentsu Agency. The success of an advertising message in capturing the audience's attention and create awareness of one set of capabilities includes an advertising content in the audio and visual elements of the use of the media, this study aims to determine the stage of making understand the message of the use of digital signage medium that has limitations on audio elements that able to highlight the visual elements that still give th eaudience an understanding in accordance with the audio function. This study used a qualitative research method with descriptive explorative design, to explain the results of the interview and observation data analysis techniques used thematic analysis. The results showed limitations in representing by the agency of visual elements on the digital signage medium  in  capturing  the  attention  of  the  audience,  persuasive,  and  increase  awareness  of  the audience for a productor service through the medium. Production strategies under taken message includes three stages which includes the step of: 1) Pre-production, 2) production, and 3) Post- Production. Implementation of the medium is seen in the field of advertising (commercial) and some other fields related to the use of digital signage. Keywords:Digital Signage,Implementation of Digital Signage,Message Creating Strategy. AbstrakPenelitian ini membahas tentang digital signage: makna, strategi pembuatan pesan dan implementasi oleh Dentsu Agency. Keberhasilan sebuah pesan iklan dalam menangkap atensi dan menciptakan awareness audiens salah satunya ditentukan dari kemampuan sebuah konten iklan dalam menonjolkan unsur audio dan visual dari penggunaan media, penelitian ini bertujuan untuk mengetahui memahami tahapan pembuatan pesan dari penggunaan medium digital signage yang memiliki keterbatasan pada unsur audio agar mampu menonjolkan unsur visual yang tetap memberikan pemahaman pada audiens sesuai dengan fungsi audio.  Penelitian ini menggunakan metode penelitian kualitatif dengan desain deskriptif ekploratif, untuk menjelaskan hasil wawancara dan observasi digunakan teknik analisis data dengan analisa tematik. Hasil penelitian menunjukkan keterbatasan agency dalam menunjukan unsur visual   pada   medium   digital   signage   dalam  menangkap   atensi   dari   audiens,   persuasif,   dan meningkatkan awareness audiens terhadap sebuah produk atau jasa melalui medium tersebut. Strategi produksi pesan yang dilakukan meliputi tiga tahapan  yang meliputi tahap : 1)  Pra produksi,  2) Produksi, dan 3) Pasca Produksi. Implementasi penggunaan medium ini dilihat dalam bidang periklanan  (komersial)  dan  beberapa  bidang  lainnya  yang  berkaitan  dengan  penggunaan  digital signage. Kata kunci : Digital Signage,Implementasi,Strategi Pembuatan Pesan.